Short-term dynamics of nano- and picoplankton in the southern Benguela upwelling system - Dames, Nicole Rebecca (Department of Biological Sciences, 2022)
Wind driven coastal upwelling influences the overall physical and chemical properties of coastal regions, as well as the small phytoplankton and microbial communities responsible for the productivity and biogeochemistry governing many of these properties. These environmental changes can influence picoplankton (0.3–3 µm) and nano-picoplankton (0.3–10 µm) at different time scales; in this thesis daily changes were of interest because of the cyclic (3–7 days) nature of wind-driven upwelling. Daily variability of picoplankton was studied during an upwelling cycle at a single station in Elands Bay. Using amplicon sequencing of the 16S and 18S rRNA gene region, as well as additional supplementary environmental data, it was found that picoplankton diversity, community structure and primary metabolism varied between the active and relaxation periods of an upwelling cycle. The results highlighted the complexity of picoplankton dynamics in variable environmental settings. However, the question then became whether nano-picoplankton dynamics were as complex in a post-upwelling setting. This was assessed in autumn (post-upwelling period) in St. Helena Bay by measuring primary productivity and nitrogen cycling over five days from three depths at a single station. Using stable isotope tracer and flow cytometry analyses it was determined that primary productivity was supported by regenerated production and that nano-picoplankton were responsible for up to 90% of the net primary production, with nanoeukaryotes and heterotrophic bacteria dominating at the surface and at depth. Increased resolution of nano-picoplankton community composition, structure and potential metabolism was obtained using metagenomic analyses of samples taken at the same depths and days as the productivity study. A strong depth-differentiation in community structure and potential metabolism was found over the five-day period, with little variability observed from day to day. Metagenome abundances of transporter genes for processes like ammonium uptake and nitrite oxidation were found to be good indicators of measured process rates using isotope tracers. This research has highlighted the complex structure of picoplankton and nano-picoplankton communities in a coastal setting, and has shown how diversity, function and biotic interactions are strongly influenced by the properties of the surrounding water column.